Repetitive schistosoma exposure causes perivascular lung fibrosis and persistent pulmonary hypertension. Issue 8 (21st April 2023) - Kumar, Rahul; Lee, Michael H.; Kassa, Biruk; Fonseca Balladares, Dara C.; Mickael, Claudia; Sanders, Linda; Andruska, Adam; Kumar, Maya; Spiekerkoetter, Edda; Bandeira, Angela; Stenmark, Kurt R.; Tuder, Rubin M.; et al.
Abstract: Background: Pulmonary hypertension (PH) can occur as a complication of schistosomiasis. In humans, schistosomiasis-PH persists despite antihelminthic therapy and parasite eradication. We hypothesized that persistent disease arises as a consequence of exposure repetition. Methods: Following intraperitoneal sensitization, mice were experimentally exposed to Schistosoma eggs by intravenous injection, either once or three times repeatedly. The phenotype was characterized by right heart catheterization and tissue analysis. Results: Following intraperitoneal sensitization, a single intravenous Schistosoma egg exposure resulted in a PH phenotype that peaked at 7–14 days, followed by spontaneous resolution. Three sequential exposures resulted in a persistent PH phenotype. Inflammatory cytokines were not significantly different between mice exposed to one or three egg doses, but there was an increase in perivascular fibrosis in those who received three egg doses. Significant perivascular fibrosis was also observed in autopsy specimens from patients who died of this condition. Conclusions: Repeatedly exposing mice to schistosomiasis causes a persistent PH phenotype, accompanied by perivascular fibrosis. Perivascular fibrosis may contribute to the persistent schistosomiasis-PH observed in humans with this disease.